Cholecystectomy in mild to moderate acute biliary pancreatitis when to intervene: early versus delayed - Khan, Kamran Hakeem; Khan, Waseem Yaar; Khan, Zahid; Shahzad, Muddasar; Khan, Shahid; Imran, Rashid (International Surgery Journal, 2020)
Background: Objective of the study was to compare the outcomes of early versus late cholecystectomy in mild to moderate acute biliary pancreatitis. Methods: This comparative prospective study was conducted at Surgical Department of Qazi Hussain Ahmed Medical Complex, Nowshera from 1st January 2018 to 31st March 2020. Patients with mild to moderate acute biliary pancreatitis (ABP) were included in the study. Patients were divided into two groups. Group 1 having patients undergoing early (operated in 7 days) and Group 2 having patients with delayed (operated after 6 weeks) laparoscopic cholecystectomy. The outcomes like hospital stay, peri and post-operative complications, recurrent cholecystitis and pancreatitis were compared. P<0.05 was considered significant. Results: A total of 300 patients were included with 150 in each group. There were 70 (46.66%) males in group 1 while group 2 consisted of 68 (45.33%) males. The median time interval of operation to the laparoscopic surgery was 5 days in group1 and 42 days in group 2. Peri operative outcomes were not significant between two groups (p=0.6). About 14 (09.63%) patients were converted to open surgery in group1 and 17 (10.53%) in group 2. Postoperative complications were also not significant between two groups (p=1.0). Group 1 had small total length of stay as compared to group 2 (p=0.006). Recurrent biliary events occurred in 63 (42.12%) patients in total with no event in group 1. Conclusions: Patients with mild to moderate ABP having early laparoscopic cholecystectomy present with reduced recurrent biliary events and the total length of hospital.